Students' Questions in Writing Center Conferences. (July 2022) - Mackiewicz, Jo; Thompson, Isabelle
Questions are an important means by which students actively participate in and exercise some control over the moment-to-moment focus of writing center conferences. Through quantitative and qualitative analysis of student questions in 35 writing center conferences, we examined the frequency and type of students' questions, finding no differences between native English speakers and non-native English speakers' overall question frequency or their use of each question type. Students used common-ground questions most frequently, and knowledge-deficit questions second-most frequently. Our qualitative analysis revealed how students used questions to coconstruct potential language for their papers and to steer the course of their conferences. It also revealed the dilemma that arises when a student's questions probe not only the tutor's writing knowledge but also their subject-matter knowledge. This study demonstrates some ways that students take power over their conferences by asking questions and indicates that tutors might expect similar question frequency and similar types of questions from NESs and NNESs. It also suggests that tutors might use the tutoring strategy of reading aloud to create conversational openings for students' questions. And it suggests potential benefits of attending to the type of questions that students use, as these types can indicate on a local level the extent of students' contribution to their papers.